Degradation kinetics of phenolic content and antioxidant activity of hardy kiwifruit (Actinidia arguta) puree at different storage temperatures. (March 2018) - Kim, Ah-Na; Kim, Hyun-Jin; Chun, Jiyeon; Heo, Ho Jin; Kerr, William L.; Choi, Sung-Gil
Abstract: The effect of storage temperature on the degradation of total phenolic content (TPC) and antioxidant activity in hardy kiwifruit ( Actinidia arguta ) puree was investigated at temperatures of 5, 15, 25, and 45 °C for 72 h. An increase in the storage temperature resulted in a decrease in the TPC and antioxidant activity of hardy kiwi puree over time. The degradation of total phenolic content and antioxidant activity followed a first-order kinetic model and the kinetic parameters such as k, t 1/2, Q 10, and Ea were calculated. The k and t 1/2 values decreased with increasing storage temperature and the Q 10 values for TPC and antioxidant activity were 1.43 and 1.43, respectively. These results indicated strong dependence on temperature of phenolic content and antioxidant activity in hardy kiwi puree. The Ea for the degradation of TPC and antioxidant activity in hardy kiwi puree were 28.15 and 29.07 kJ/mol, respectively. Major phenolic compounds in hardy kiwi identified by UPLC-Q-TOF MS were epicatechin, procyanidin B type, procyanidin trimers, catechin, chlorogenic acid, and isoquercetin. These compounds were degraded with increase in storage temperature and time. This result is consistent with kinetic studies on phenolic content and antioxidant activity. Highlights: TPC and DPPH of hardy kiwi reduced during storage and showed temperature dependency. Q 10 and Ea for TPC were 1.43 and 28.15 kJ/mol, while DPPH were 1.43 and 29.07 kJ/mol. Major phenolics in hardy kiwi were epicatechin, procyanidins, and chlorogenic acid. Chlorogenic acid was more stable than other phenolic compound in hardy kiwi.